Using Shrub Clearing, Draining, and Herbivory to Control Bramble Invasion in Mediterranean Dry Grasslands - Masson, Solène; Mesléard, François; Dutoit, Thierry (Environmental management (New York), 2015)
For centuries, the dry grassland of the plain of La Crau (south-eastern France) has been subjected to numerous disturbances resulting in the destruction and the fragmentation of this emblematic rangeland ecosystem of the Mediterranean. Today, this ecosystem is facing a new threat from a proliferating native species, the bramble ( Rubus ulmifolius Schott), which preferentially colonizes areas that were formerly cultivated and/or exposed to water infiltration. To identify a strategy for effective control of this colonization, in situ experiments testing disturbance regimes (shrub clearing and/or mixed grazing by sheep and goats) combined with the control of access to water resources (with or without drainage trenches) were undertaken between 2010 and 2013. Only clearing and grazing combined over 3 years led to significant changes in vegetation height and bramble cover as well as modifications in the floristic composition, diversity, similarity, and richness of the plant community. Neither a clearing operation carried out in 2010 alone, nor grazing alone, reduced bramble cover, and neither treatment increased the species richness of the plant community. Similarly, digging drainage trenches had no significant impact either on the plant community or on bramble cover. Our study suggests that only annual mechanical clearing coupled with sheep and goats grazing can significantly reduce bramble cover. This combined restoration treatment needs to be applied for at least 3 consecutive years to induce significant changes and enable this ecosystem to return to the dry grassland succession.